Budaya Penggemar di Twitter: Etnografi Virtual pada Penggemar NCT di Twitter - Sakina, Rizqi Aulia; Widyasari, Wulan (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to analyze NCTzen's online fan culture experience on Twitter. NCTzen is one of the fandoms from the K-pop group called NCT. As fans, NCTzen always tries to get knowledge and information related to NCT. They use Twitter as their medium for doing their activities as fans. NCTzen actively contributed to the development of content media and expanded the scope and impact of text media related to NCT. The method used in this study is a qualitative method with a virtual ethnographic research type. This method uses data collection techniques such as participatory observation, interviews, and documentation. The data analysis technique used is cyber-media analysis. The findings of this study suggest that NCTzen fan culture is a component of participatory culture; it takes shape in affiliation, expressiveness, group problem-solving, and circulation in NCTzen fan activities. Affiliation occurs when NCTzens who carry out their activities online use attributes related to NCT to show themselves as part of the fandom and utilize Twitter features to interact and share with fellow NCTzens. Expression occurs when NCTzens produce creative works whose sources are taken from official NCT content and then shared again through fan accounts in various forms. Such as fan edits, fan works, as well as content and translated texts for NCT content. Collaborative problem-solving is done by working together to support and protect NCT. Such as working together in streaming so that NCT songs enter the charts, voting so that NCT wins awards, and reporting and blocking so that no baseless rumors circulate. The circulation circulating among NCTzens is a thread that informs about matters related to NCT.NCTzen's online fan culture brings together NCTzens from various backgrounds and perspectives so that media content is produced based on the experiences and interpretations of each NCTzen.